„Is ja cool" - der Wandel der Sprache in der Moderne - Utri, Reinhold (Glottodidactica, 2008)
The author's diagnosis of the modern German language has found that it is full of English terms and phrases, especially in the mass media, where many of them are already intruding into the everyday language. Some language researchers fear the worst - but is this fear really justified? The author of this article explains the old tendency of traditionalists to keep the language „clean" and not to accept words which are borrowed from other fashionable" languages. Because of globalization and modern technology there are more English words coming into the German language. Another reason is that the youth find English more fashionable and attractive. The process of borrowing a word from another language is usually a slow process and many words are not kept and disappear later. Those that are practical and useful are kept and this is shown in the case with Anglicism. Although it is sometimes difficult to put the English word into the German Grammar structure, the average German is able to incorporate them into their language. This importing and exporting of words (but why only from English?) is only an example of an evolving language that changes every day.